Evaluation of Students’ Understanding of Thermal Concepts in Everyday Contexts - Chu, Hye-Eun; Treagust, David; Yeo, Shelley; Zadnik, Marjan (Routledge, 2012)
The aims of this study were to determine the underlying conceptual structure of the thermal concept evaluation (TCE) questionnaire, a pencil-and-paper instrument about everyday contexts of heat, temperature, and heat transfer, to investigate students’ conceptual understanding of thermal concepts in everyday contexts across several school years and to analyse the variables—school year, science subjects currently being studied, and science subjects previously studied in thermal energy—that influence students’ thermal conceptual understanding. The TCE, which was administered to 515 Korean students from years 10–12, was developed in Australia, using students’ alternative conceptions derived from the research literature. The conceptual structure comprised four groups—heat transfer and temperature changes, boiling, heat conductivity and equilibrium, and freezing and melting—using 19 of the 26 items in the original questionnaire. Depending on the year group, 25–55% of students experienced difficulties in applying scientific concepts in everyday contexts. Years of schooling, science subjects currently studied and physics topics previously studied correlated with development of students’ conceptual understanding, especially in topics relating to heat transfer, temperature scales, specific heat capacity, homeostasis, and thermodynamics. Although students did improve their conceptual understandings in later years of schooling, they still had difficulties in relating the scientific concepts to their experiences in everyday contexts. The study illustrates the utility of using a pencil-and-paper questionnaire to identify students’ understanding of thermal concepts in everyday situations and provides a baseline for Korean students’ achievement in terms of physics in everyday contexts, one of the objectives of the Korean national curriculum reforms.